2013
DOI: 10.1093/hmg/ddt309
|View full text |Cite
|
Sign up to set email alerts
|

Altered 2-thiouridylation impairs mitochondrial translation in reversible infantile respiratory chain deficiency

Abstract: Childhood-onset mitochondrial encephalomyopathies are severe, relentlessly progressive conditions. However, reversible infantile respiratory chain deficiency (RIRCD), due to a homoplasmic mt-tRNAGlu mutation, and reversible infantile hepatopathy, due to tRNA 5-methylaminomethyl-2-thiouridylate methyltransferase (TRMU) deficiency, stand out by showing spontaneous recovery, and provide the key to treatments of potential broader relevance. Modification of mt-tRNAGlu is a possible functional link between these two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 28 publications
1
45
0
1
Order By: Relevance
“…17 In vitro studies in patient fibroblasts showed that copper 18 and copper with bezafibrate supplementation rescued cells harboring mutations in SCO2 encoding a COX copper-chaperone 19 while L-cystein supplementation improved mitochondrial function in cells with TRMU mutations. 20 However, as the COX6B1 defect does not cause LS and the protein is not a copper chaperone but an integral COX subunit, we evaluated a number of other potentially beneficial molecules for their ability to improve mitochondrial function in the patient's fibroblasts. The significantly beneficial effect of AICAR on ATP content, and resveratrol on both ATP content and growth resembles the effect of these mitochondrial biogenesis inducers, on defects due to GFM1 and MRPS22, mutations in the mitochondrial translation machinery.…”
Section: Discussionmentioning
confidence: 99%
“…17 In vitro studies in patient fibroblasts showed that copper 18 and copper with bezafibrate supplementation rescued cells harboring mutations in SCO2 encoding a COX copper-chaperone 19 while L-cystein supplementation improved mitochondrial function in cells with TRMU mutations. 20 However, as the COX6B1 defect does not cause LS and the protein is not a copper chaperone but an integral COX subunit, we evaluated a number of other potentially beneficial molecules for their ability to improve mitochondrial function in the patient's fibroblasts. The significantly beneficial effect of AICAR on ATP content, and resveratrol on both ATP content and growth resembles the effect of these mitochondrial biogenesis inducers, on defects due to GFM1 and MRPS22, mutations in the mitochondrial translation machinery.…”
Section: Discussionmentioning
confidence: 99%
“…87,109 In line with this, TRMU, which carries the sulfur moiety that is finally transferred to mt-tRNAs, has been suggested to be involved in the assembly of enzyme complexes containing iron-sulfur clusters, since an intermediate of the OXPHOS Complex II accumulates in TRMU-depleted cells. 8,95 However, this hypothesis does not explain why the accumulation of subunits of complex IV, which does not contain an iron-sulfur center, is also affected in the depleted cells. 95 Hence further work is required to clarify the hypothetical role of TRMU in sulfur trafficking.…”
Section: Glumentioning
confidence: 96%
“…8,95 However, this hypothesis does not explain why the accumulation of subunits of complex IV, which does not contain an iron-sulfur center, is also affected in the depleted cells. 95 Hence further work is required to clarify the hypothetical role of TRMU in sulfur trafficking.…”
Section: Glumentioning
confidence: 96%
See 1 more Smart Citation
“…Inactivation of the s 2 U pathway in E. coli is not lethal, but it causes growth defects associated with loss of reading frame maintenance (36,37). Similarly, inactivation of the nonessential 2-thiouridylase gene MTU1, while leaving the organism viable, causes respiratory defects in yeast and humans (38,39). On the other hand, the archaeal 2-thiouridylase gene Ncs6 is essential in Methanococcus maripaludis (33) and necessary for growth at high temperatures in Haloferax volcanii (34).…”
Section: Levels Of Expression Of Mnma Affects Abundance Of Smentioning
confidence: 99%